2021
DOI: 10.23876/j.krcp.20.143
|View full text |Cite
|
Sign up to set email alerts
|

Are there any further modalities for prediction of subclinical volume overload in advanced stages of chronic kidney disease?

Abstract: Background: Subclinical volume overload in chronic kidney disease (CKD) patient represents a debatable issue. Although many tools were used to detect volume overload in such patients, many non-specific results were due to presence of comorbidities. Bioimpedance spectroscopy is an objective fluid status assessment method, which is shown superior to classical methods in many studies. Combining some of these tools may improve their accuracy and specificity. Inferior vena cava collapsibility index (IVCCI) with bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A recent study by Wang et al on 129 HD patients documented the predictive value of NT-pro-BNP in the assessment of volume overload in hemodialysis patients with or without EF declines [36]. Baki et al found that combined elevation of BNP level and decreased IVC collapsibility index were sensitive markers for subclinical volume overload detection in CKD patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wang et al on 129 HD patients documented the predictive value of NT-pro-BNP in the assessment of volume overload in hemodialysis patients with or without EF declines [36]. Baki et al found that combined elevation of BNP level and decreased IVC collapsibility index were sensitive markers for subclinical volume overload detection in CKD patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular volume overload has been reported even in early stage of CKD [ 4 ]. However, a significant number of patients have subclinical volume overload without evident clinical signs [ 5 , 6 ]. Such existence of extracellular volume increase can be detected by noticing impressive blood pressure reduction when diuretics are added in a situation of uncontrolled hypertension during the use of antihypertensive agents other than diuretics [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant number of patients have subclinical volume overload without evident clinical signs [ 5 , 6 ]. Such existence of extracellular volume increase can be detected by noticing impressive blood pressure reduction when diuretics are added in a situation of uncontrolled hypertension during the use of antihypertensive agents other than diuretics [ 4 , 5 ]. Doubt on the effectiveness and safety related to use of diuretics in CKD patients has been present for many years.…”
Section: Introductionmentioning
confidence: 99%